Policy regimes, inequality, poverty and growth: The Chilean experience, 1973 - 2010 - Dante Contreras; Ricardo Ffrench-Davis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Since the 1970s, Chile has exhibited a highly skewed income distribution accompanied with strong fluctuations over time. Although income distribution worsened notably in the 1970s-80s, a significant improvement was recorded in the first half of the 1990s, resulting from better economic and social policies in the return to democracy. Nonetheless, Chile still faces significant challenges to improve development. There must be an active macroeconomic policy focused on the real economy. Chile also needs profound microeconomic reforms, including (i) capital markets, developing long-term financing channels for small businesses; (ii) radical progress in quality of education and labour training; and (iii) vigorous public support for innovation.
Keywords: D31; E2; D04; 330; income distribution; macroeconomic policy; microeconomic policies; Einkommensverteilung; Armut; Wirtschaftswachstum; Wirtschaftspolitik; Chile; Einkommensverteilung; Wirtschaftspolitik; Mikroökonomische Fundierung; Chile